Pre-service Music Teachers' Metaphoric Perception for the Musical Instrument Education - Demet Girgin (Anı Publishing, 2019)
This study aimed to determine pre-service music teachers' perception for the musical instrument education by means of metaphors. The study sample included 95 pre-service music teachers in the Music Teaching Program of the Fine Arts Teaching Department at Balıkesir University's Necatibey Education Faculty. This is a qualitative study. In the study data were collected by having the participants complete the sentences. "A teacher is like a... because...". The data were examined using content analysis method. The data has been analysed through content analysis technique under such titles as labeling, classification, category development, validity and reliability of the supply, data transfer to computer. The pre-service music teachers produced 42 metaphors. These metaphors were classified into six theoretical categories by shared characteristics. At the end of the research, it was understood that pre-service teachers have a perception that musical instrument education is; a way of expressing change and development, a way of expressing infinity, a way of expressing obligation, a way of expressing improvement, a way of expressing emotion, a way of expressing patience. The most common metaphors developed by the students are sea, trea, water, and space. It has been determined that the meanings assigned to the musical instrument education by the pre-service music teachers are positive in general.